(untitled) (Economics and region, 2017)
UDC 911.3 JEL L083, О31,О33 Chernysh, D.Sc. (Economics), Associate Professor. A. Hliebova, PhD (Economics). Makhovka, PhD (Economics), Senior Lecturer. Poltava National Technical Yurii Kondratiuk University. Innovational Technologies for the Travel Industry: Security and Sustainable Development. The article explores theoretical and practical aspects of the development of innovative technologies in tourism at the present stage. Systematization of the basic directions of innovative technologies is carried out, at the present stage they allow to receive a synergetic effect in tourism due to introduction in related industries. The authors’ approach to the systematization of innovative technologies is proposed. Keywords: tourism, innovative technologies, sustainable development, innovation, competitive advantage.